The use of virtual laboratories in teaching chemistry to secondary school students from the point of view of chemistry teachers in the State of Qatar - Gasmelsid, Wasfi Abdelmageed; Saeed, Yasir Mohammed (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the use of virtual laboratories in teaching chemistry to secondary school students. The study used the descriptive analytical method, and the study population consisted of male chemistry teachers in secondary schools in each of the cities (Al-Rayyan, Doha, Mesaieed) in the State of Qatar. The study used the questionnaire as a tool for the study, the study reached a number of results, the most important of which are: Scientific laboratories are available in secondary schools in the State of Qatar, the school administration contributes to providing scientific laboratories, the school administration provides raw materials for conducting experiments in laboratories, experiments conducted in the laboratory attract students’ attention and provide Time for the teacher to explain, in light of the results of the study The study recommends taking advantage of virtual laboratories to overcome the problems and obstacles facing students in teaching chemistry, training employees to design computer programs at the Ministry of Education to design virtual laboratories for all educational levels, the need to use laboratory technology that has proven effective in achieving the goals of teaching science in general and chemistry In particular, communication and teamwork skills should be enhanced in virtual labs.
Keywords: Virtual labs; e-learning; virtual education; Computer simulation